Floating catalyst CVD synthesis of single walled carbon nanotubes from ethylene for high performance transparent electrodes. Issue 20 (16th May 2018) - Hussain, Aqeel; Liao, Yongping; Zhang, Qiang; Ding, Er-Xiong; Laiho, Patrik; Ahmad, Saeed; Wei, Nan; Tian, Ying; Jiang, Hua; Kauppinen, Esko I.
Abstract : Manufacturing of high performance transparent conducting electrodes from very long and a high proportion of individual SWCNTs using the ethylene floating catalyst CVD process. Abstract : We have developed the floating catalyst chemical vapor deposition (FCCVD) synthesis of single walled carbon nanotubes (SWCNTs) using C2 H4 hydrocarbon as a carbon source and iron nanoparticles as the catalyst in an environmentally friendly and economical process. For the first time, ethylene was used as the only carbon source in FCCVD with N2 as the main carrier gas. No sulphur and less than 15% H2 in a N2 carrier gas were used. By varying the ferrocene concentration, the diameter of the SWCNTs was tuned in the range of 1.3–1.5 nm with the optimized control of ferrocene concentration. The process produced SWCNTs with an average length of 13 μm and with a low level of bundling, that is a high proportion (28%) of individual tubes. The electron diffraction (ED) pattern indicated a random chirality distribution of the tubes between armchair and zigzag structures. The ED analysis also revealed that 35–38% of tubes are metallic. As a result of having long SWCNTs with a low level of bundling and a high fraction of metallic tubes, we produced a highly conductive transparent film with a sheet resistance of 51 Ohm per sq. for 90% transmission at 550 nm after HNO3 treatment, this being one of the lowest sheet resistance values reported for SWCNT thin films.